One Colour, (at Least) Two Minerals: A Study of Mulberry Rock Art Pigment and a Mulberry Pigment 'Quarry' from the Kimberley, Northern Australia. (12th December 2013) - Huntley, J.; Aubert, M.; Ross, J.; Brand, H. E. A.; Morwood, M. J.
<x xml:space="preserve">Abstract</x> Distinctive mulberry paintings found in northern Australia, particularly those of the Kimberley region, have been argued to represent some of the oldest surviving rock art on the continent. Significant research efforts continue to focus on resolving the age of these motifs, but comparatively little attention has been given to understanding their physical composition and potential source(s). In a pilot investigation, we conclude that (at least) two mineralogically distinct mulberry pigments occur in Gwion motifs and demonstrate that their major components can be indicatively chemically differentiated, non‐invasively. Characterization of a 'quarried' mulberry ochre source demonstrates that these pigments occur locally as natural minerals.